ASTEROID MEGA-IMPACTS AND PRECAMBRIAN BANDED IRON FORMATIONS: 2.63 GA AND 2.56 GA IMPACT EJECTA/FALLOUT AT THE BASE OF BIF/ARGILLITE UNITS, HAMERSLEY BASIN, PILBARA CRATON, WESTERN AUSTRALIA - Glikson A.; Vickers J. (My University, 2007)
The temporal association between late Archaean to earliest Proterozoic asteroid impact ejecta/fallout units and overlying banded iron formations suggests that, in some instances, these impacts were closely followed by significant transformation in the nature of source terrains of the sediments. The Jeerinah Impact Layer (JIL) [B.M. Simonson, D. Davies, S.W. Hassler, Discovery of a layer of probable impact melt spherules in the late Archean Jeerinah Formation, Fortescue Group, Western Australia. Aust. J. Earth Sci. 47 (2000) 315-325; B.M. Simonson, S.W. Hassler, Revised correlations in the early Precambrian Hamersley Basin based on a horizon of resedimented impact spherules. Aust. J. Earth Sci. 44 (1997) 37-48; B.M. Simonson, B.P. Glass, Spherule layers - records of ancient impacts. Ann. Rev. Earth Planet. Sci. 32 (2004) 329-361; A.Y. Glikson, Early Precambrian asteroid impact-triggered tsunami: excavated seabed, debris flows, exotic boulders, and turbulence features associated with 3.47-2.47 Ga-old asteroid impact fallout units, Pilbara Craton, Western Australia. Astrobiology 4 (2001) 19-50; S.W. Hassler, B.M. Simonson, D.Y. Sumner, D. Murphy, Neoarchaean impact spherule layers in the Fortescue and Hamersley Groups, Western Australia: stratigraphic and depositional implications of re-correlation. Aust. J. Earth Sci. 52 (2005) 759-772; B. Rasmussen, C. Koeberl, Iridium anomalies and shocked quartz in a late Archean spherule layer from the Pilbara Craton: new evidence for a major asteroid impact at 2.63 Ga. Geology 32 (2004) 1029-1032; B. Rasmussen, T.S. Blake, I.R. Fletcher, U-Pb zircon age constraints on the Hamersley spherule beds: Evidence for a single 2.63 Ga Jeerinah-Carawine impact ejecta layer. Geology, 33 (2005) 725-728.] overlies an argillite-dominated unit (Jeerinah Formation, 2684 ± 6 Ma [A.F. Trendall, W. Compston, D.R. Nelson, J.R. deLaeter, V.C. Bennett, SHRIMP zircon ages constraining the depositional chronology of the Hamersley Group, Western Australia. Aust. J. Earth Sci. 51 (2004) 621-644.]) and lies directly below a thin volcanic tuff (2629 ± 5 Ma, [A.F. Trendall, W. Compston, D.R. Nelson, J.R. deLaeter, V.C. Bennett, SHRIMP zircon ages constraining the depositional chronology of the Hamersley Group, Western Australia. Aust. J. Earth Sci. 51 (2004) 621-644.]) and banded iron formation (BIF) (upper part of Marra Mamba Iron Formation, 2597 ± 5 Ma [A.F. Trendall, W. Compston, D.R. Nelson, J.R. deLaeter, V.C. Bennett, SHRIMP zircon ages constraining the depositional chronology of the Hamersley Group, Western Australia. Aust. J. Earth Sci. 51 (2004) 621-644.]). The Spherule Marker Bed (SMB) [B.M. Simonson, Geological evidence for an early Precambrian microtektite strewn field in the Hamersley Basin of Western Australia. Geol. Soc. Am. Bull. 104 (1992) 829-839; B.M. Simonson, S.W. Hassler, K.A. Schubel, Lithology and proposed revisions in stratigraphic nomenclature of the Wittenoom Formation (Dolomite) and overlying formations, Hamersley Group, Western Australia. Geol. Surv. W. Aust. Rep. 345 (1993) 65-79; S.W. Hassler, B.M. Simonson, D.Y. Sumner, D. Murphy, Neoarchaean impact spherule layers in the Fortescue and Hamersley Groups, Western Australia: stratigraphic and depositional implications of re-correlation. Aust. J. Earth Sci. 52 (2005) 759-772. [5]], which includes two impact cycles [A.Y. Glikson, Early Precambrian asteroid impact-triggered tsunami: excavated seabed, debris flows, exotic boulders, and turbulence features associated with 3.47-2.47 Ga-old asteroid impact fallout units, Pilbara Craton, Western Australia. Astrobiology 4 (2001) 19-50.], is located at the top of a carbonate/calcareous siltstone-dominated sequence (Bee Gorge Member, Wittenoom Formation, 2565 ± 9 Ma [A.F. Trendall, W. Compston, D.R. Nelson, J.R. deLaeter, V.C. Bennett, SHRIMP zircon ages constraining the depositional chronology of the Hamersley Group, Western Australia. Aust. J. Earth Sci. 51 (2004) 621-644.]) and below a carbonate-poor siltstone-chert-BIF sequence (Mount Sylvia Formation, Bruno's Band [BIF], Mount McRae Shale, 2504 ± 5 Ma [B. Rasmussen, T.S. Blake, I.R. Fletcher, U-Pb zircon age constraints on the Hamersley spherule beds: Evidence for a single 2.63 Ga Jeerinah-Carawine impact ejecta layer. Geology, 33 (2005) 725-728.]). No ferruginous sediments overlie impact layers hosted by stromatolitic carbonates (< 2.63 Ga microkrystite spherule-bearing Carawine mega-breccia, east Hamersley Basin; ~ 2.6-2.65 Ga Monteville impact layer; 2567 Ma Reivilo Formation, west Griqualand Basin, Transvaal) - a lack possibly attributable to enclosed oxygenated high-pH reef environment. Barring a possible presence of undocumented hiatuses between the impact layers and directly overlying units, and within the accuracy limits of U-Pb zircon age data, it follows that the JIL and SMB mega-impacts were succeeded by enhanced supply of ferruginous and clastic materials. The location of 5 out of 8 Archaean to earliest Proterozoic impact fallout/ejecta units below iron-rich sediments [A.Y. Glikson, Asteroid impact ejecta units overlain by iron-rich sediments in 3.5-2.4 Ga terrains, Pilbara and Kaapvaal cratons: Accidental or cause-effect relationships? Earth Planet. Sci. Lett. 246 (2006) 149-160.], including 3.47 Ga, 3.26 Ga, 3.24 Ga, 2.63 Ga and 2.56 Ga units, unless accidental, suggests enrichment of sea water in soluble ferrous iron, possibly derived from impact-triggered mafic volcanic and hydrothermal activity. The scarcity of shocked quartz grains in the ejecta suggests impacts occurred in oceanic regions of the late Archaean Earth [A.Y. Glikson, Early Precambrian asteroid impact-triggered tsunami: excavated seabed, debris flows, exotic boulders, and turbulence features associated with 3.47-2.47 Ga-old asteroid impact fallout units, Pilbara Craton, Western Australia. Astrobiology 4 (2001) 19-50; A.Y. Glikson, Oceanic mega-impacts and crustal evolution, Geology 27 (1999) 341-387; B.M. Simonson, D. Davies, M. Wallace, S. Reeves, S.W. Hassler, Iridium anomaly but no shocked quartz from late Archean microkrystite layer: oceanic impact ejecta? Geology 26 (1998) 195-198.]. Should further examples of sedimentary facies changes associated with large impact events be identified, the impact factor will need to be taken into account in accounting for the crustal transformations during the transition from the end-Archaean to the earliest Proterozoic. © 2006 Elsevier B.V. All rights reserved.
Keywords: ASTEROID IMPACT; BANDED IRON FORMATION; HAMERSLEY; PILBARA; WESTERN AUSTRALIA; Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Precambrian::Archean; Докембрий::Архей